EDOT-based conjugated polymers accessed via C–H direct arylation for efficient photocatalytic hydrogen production - Tan, Zhi-Rong; Xing, Yu-Qin; Cheng, Jing-Zhao; Zhang, Guang; Shen, Zhao-Qi; Zhang, Yu-Jie; Liao, Guangfu; Chen, Long; Liu, Shi-Yong (Chemical science (Cambridge), 2022)
3,4-Ethylene dioxythiophene (EDOT), as a monomer of commercial conductive poly(3,4-ethylene dioxythiophene) (PEDOT), has been facilely incorporated into a series of new π-conjugated polymer-based photocatalysts, i.e. , BSO 2 –EDOT, DBT–EDOT, Py–EDOT and DFB–EDOT, through atom-economic C–H direct arylation polymerization (DArP). The photocatalytic hydrogen production (PHP) test shows that donor–acceptor (D–A)-type BSO 2 –EDOT renders the highest hydrogen evolution rate (HER) among the linear conjugated polymers (CPs) ever reported. A HER up to 0.95 mmol h −1 /6 mg under visible light irradiation and an unprecedented apparent quantum yield of 13.6% at 550 nm are successfully achieved. Note that the photocatalytic activities of the C–H/C–Br coupling-derived EDOT-based CPs are superior to those of their counterparts derived from the classical C–Sn/C–Br Stille coupling, demonstrating that EDOT is a promising electron-rich building block which can be facilely integrated into CP-based photocatalysts. Systematic studies reveal that the enhanced water wettability by the integration of polar BSO 2 with hydrophilic EDOT, the increased electron-donating ability by O–C p–π conjugation, the improved electron transfer by D–A architecture, broad light harvesting, and the nano-sized colloidal character in a H 2 O/NMP mixed solvent rendered BSO 2 –EDOT as one of the best CP photocatalysts toward PHP.